Women's Economic Empowerment and Food Security in the Siring Floating Market: A Socio-Religious Analysis via Qira'ah Mubadalah - Umaima; Nurmianti Fadli (LPPM IAIN Parepare, 2026)
Women’s participation in public economic activities in Muslim societies is often shaped by socio-religious norms confining them to household roles. This study examines female traders at Siring Floating Market, South Kalimantan, and their contribution to local food security within this context. It explores how women navigate theological interpretations used to justify role restrictions, reflected in daily economic practices. Using qualitative methods, observation and semi-structured interviews, this research applies Qira’ah Mubadalah as a reciprocal interpretative framework, alongside socio-cultural gender perspectives, prioritising relational ethics over rigid scripture readings. Findings show that women significantly sustain local food systems through production, distribution, and preserving traditional culinary practices, while simultaneously challenging hadith interpretations that limit women’s mobility and economic participation. A mubadalah-based reading supports gender reciprocity, ethical accountability, and inclusive socio-economic engagement. The study contributes to debates on gender justice and social inclusion, highlighting the importance of recognising women’s economic roles in community food security and offering insights for more inclusive socio-religious frameworks in the Global South.